2015
DOI: 10.1309/lmfn8d17sohqhgrp
|View full text |Cite
|
Sign up to set email alerts
|

Resistance-Gene Cassettes Associated WithSalmonella entericaGenotypes

Abstract: The presence of a few common and new pulsotypes among the isolates suggests the emergence and spread of new clones of S. enterica in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These V. cholerae isolates have been genotyped and it has been noted that dominant strains have been changing gradually to Inaba (Table 1). It was demonstrated that these infections had been transmitted by foreign travellers [22], [24].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These V. cholerae isolates have been genotyped and it has been noted that dominant strains have been changing gradually to Inaba (Table 1). It was demonstrated that these infections had been transmitted by foreign travellers [22], [24].…”
Section: Resultsmentioning
confidence: 99%
“…Genotyping of isolates was performed by PFGE using PulseNet standard procedure for V. cholerae specimens [30]. The whole agarose-embedded genomic DNA from V. cholerae was prepared and the previously described procedure [24], [26], [27], [31] was carried out. The fingerprinting patterns in the PFGE gels were re-analysed using the computer software package BioNumerics 6.6 (Applied Maths, Keistraat 120.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations